Management of Rejected Plastic Packaging as an Alternative Industrial Fuel - Yansen, Albert (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Solutions are needed to cope with the reject plastic packing waste that the plastic packaging industry produces. Using rejected plastic packaging waste as a coal substitute and lowering environmental pollution to feed a cement kiln by co-processing method are the goals of this project in West Java (Indonesia). Rejected plastic packaging is shredded, wrapped in large plastic packaging, sent to the cement factory by truck, and when it arrives at the cement factory, the plastic waste is mixed with other solid waste and immediately used as alternative fuel. This stage is a co-processing method applied in the process of managing rejected plastic packaging. With a length of less than 5 cm, the resultant dry plastic shreds. 8.269 kcal/kg of calories, 0.54% moisture, 5.39% ash content, and 0.13% sulfur were found in the study's results. According to these findings, waste from rejected packaging plastic can be utilized to substitute coal in the cement industry (kiln) as an alternative fuel without having any negative effects.